Is promotion competition responsible for local protectionism in China? - XiaoBing, Le; Aralas, Sarma Binti (Asian Development Policy Review, 2024)
This study investigates the promotion competition for local protectionism in China. Since the personnel evaluation criteria in China shifted from political loyalty to economic performance, local governments strive to pursue regional tax benefits and political promotion opportunities, often adopting a range of protective measures to support the economic development of their regions. However, these actions can significantly impede the normal functioning of the market and result in local protectionism. Addressing local protectionism is crucial for accelerating the establishment of a nationally unified market characterized by fair competition and full openness. Overcoming local protectionism necessitates not only an environment conducive to fair competition, but also the active coordination of local officials. This study investigates the factors that influence local protectionism in China using the spatial econometric methods. Applying provincial panel data spanning the years 2003 to 2019, the study focuses on promotion competition among local officials that contributes to local protectionism. The results of an empirical study show that local protectionism is spatially related between regions. This means that when foreign government implements local protection policies, the local government responds with similar measures, and the level of response varies between regions. Additionally, the spatial spillover effect of promotion competition on local protectionism is found to be significant, with the impact displaying variations across different phases. The findings offer a new understanding of the issue of local protectionism.